Reversible blazer / Wan Hasmat Wan Hasan ... [et al.] - Wan Hasan, Wan Hasmat; Khairil Anwar, Nur Anisah; Salim, Norhidayahtul Sakinah; Ali Sidek, Nur Aina Madihah; Hairol, Nur Atiqa (Bahagian Penyelidikan dan Jaringan Industri, UiTM Melaka, 2022)
The initiative to broaden the definition of clothing industry is controversial, as the promotion of sustainable life is increasing. As more fast-clothing apparel gets attention compared to ethical clothing, it disrupts the objective of several organizations that wanted to contribute in sustaining a better environment for the earth. Besides, a facile lifestyle approaching a minimalist future is vital to boost the industry readiness, specifically the endemic phase. We have to visualize that, ten years from now, the existence of a regular shirt may be extinct to fit future expectations. Thus, the VMIIEX effort in expanding the innovative skills among students, help the world to recognize and value youths’ outlook to contribute intensively building a new vision. Henceforth, with the aid and guidance of authorized organizations, our strive in making the idea of Reversible Blazer into reality may benefit others.